"Compassionate Companion, Familiar Friend": The Turin Safīna (Biblioteca Reale Ms. Or. 101) and Its Significance - Teece, Denise-Marie (Muqarnas, 2019)
This article examines some of the more significant aspects of Turin Safīna manuscript Biblioteca Reale Ms. Or. 101. One of these is its unique and important six-page preface, which refers to the manuscript as a safīna (ship or vessel) and explains in poetic language why some Persian manuscripts are referred to using this term. In addition to this significant preface, which is translated and analyzed in the first half of the article, the manuscript also exhibits delicate illuminations and calligraphy work that may be connected to a network of artist-families active in western Persia (primarily in the region of Shiraz) around the time of its completion. The second half of this article revisits the careers of some of these artists, and discusses the broader artistic context for the creation of the Turin safīna manuscript. Special attention will be given to the careers of the illuminator known as Ruzbehanal-Modhahheb, and his calligrapher father Naʿim al-Din al-Kateb.